2011
DOI: 10.1590/s0004-27492011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and ocular perfusion during hemodialysis

Abstract: RESUMO Descritores: Diálise renal; Insuficiência renal crônica; Pressão intraocular; Glaucoma ABSTRACTAim: To evaluate the intraocular pressure and ocular perfusion pressure during a hemodialysis. Methods: Sixty-seven eyes from thirty-five patients were evaluated at the beggining of hemodialysis, 2 hours and 4 hours after initiation. Intraocular pressure was evaluated using a Tonopen. Systolic and diastolic arterial pressures were measured with a manual sphygmomanometer. The ocular perfusion pressure was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
0
18
0
5
Order By: Relevance
“…The ocular perfusion pressure (OPP) was calculated by measuring the difference between 2 out of 3 of the MBP and IOP values. [24][25][26] All measurements were performed between 9 AM and 11 AM.…”
Section: Examination Protocol and Study Measurementsmentioning
confidence: 99%
“…The ocular perfusion pressure (OPP) was calculated by measuring the difference between 2 out of 3 of the MBP and IOP values. [24][25][26] All measurements were performed between 9 AM and 11 AM.…”
Section: Examination Protocol and Study Measurementsmentioning
confidence: 99%
“…The ocular perfusion pressure (OPP) was calculated by measuring the difference between two out of three of the mBP and IOP values. 8,9 The subfoveal CT (SFCT) was measured using SD-OCT (Spectralis, wavelength: 870 nm; Heidelberg Engineering Co, Heidelberg, Germany) with enhanced depth-imaging modality. The procedure for EDI-OCT measurement has been described previously.…”
Section: Examination Protocol and Study Measurementsmentioning
confidence: 99%
“…The authors concluded that the shifting of water from the interstitial fluid into the plasma results in a drop in tear secretion, aqueous production, and corneal hydration. In another study, researchers reported that the IOP, OPP, and SAP did not vary significantly in ESRD patients during hemodialysis (25) . We also did not observe a significant change in IOP; however, OPP, SAP, DAP, and MAP decreased significantly.…”
Section: Discussionmentioning
confidence: 93%